Estratégias de Comunicação e Ativismo Feminino na Esfera Pública Midiática: Estudo sobre a participação de jovens negras no hip-hop, a construção de identidades e sua presença na internet. - Silva, Célia Regina da (2011)
This study attempts to immerse into the experiences of women who take part in the hip-hop cultural movement. In particular, it has intended to discuss the organization of interactive arrangements and relations of belonging, presence and empowerment. Another goal in the research was to understand the interactive experience of women in social networks and their implications in contemporary youth cultural practices exercised periphery of the city, which serves as reference in the struggle against gender inequalities and racism. Finally, it has been investigated the connections between social interactions, culture and political action in the public sphere. The experience of identity, gender and participation in the online universe was constructed from readings on identity politics, feminist theory, and the social interactions afforded by ICTs. It was made contacts with different types of women through interviews, questionnaires, participation in events, visits to sites, and participation in the online social network. Among the results of the research can be highlighted the strengthening of actions and icons in the dissemination of hip-hop culture and the proposition about the political and social activism.